The system of cognitive influence of the Russian Federation on Ukraine and the audiences of other states: the security dimension - Semenenko, Oleh; Horbatiuk, Volodymyr; Tarasov, Oleh; Stolinets, Serhii; Musienko, Volodymyr; Prokhorsky, Serhiy (Social Development and Security, 2025)
Purpose: is a comprehensive analysis of the system of cognitive influence of the Russian Federation on Ukraine and the audience of other states through the prism of the security dimension. Method: analysis; synthesis; comparison; formalization and evaluation of effectiveness; expert survey; abstraction and conjunctural analysis (thinking). Findings: Results of the assessment of the main aspects and their components regarding the cognitive impact of Russia on the Ukrainian audience; Results of the assessment of the main aspects and their components regarding the cognitive impact of Russia on the audience of Western and European countries; Results of the assessment of the main aspects and their components regarding the cognitive impact of Russia on the audience of countries of the world that were neutral to the war in Ukraine. Theoretical implications: selecting The issue of how Russia uses informational and psychological, propaganda and disinformation tools to manipulate public opinion and form a narrative that is beneficial to itself in Ukraine, Western countries and neutral states is identified. Paper type: theoretical, descriptive, practical, methodical.